The ethicals conflict and its solution in Radical Behaviorism (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
Deriving the good of the culture from his explanatory framework, Skinner bases his Ethics. The author establishes that the survival of the culture must be the value that guides someone who is in the position to design cultural practices. In this way, the good of the culture and some personal goods may be contradictory. This fact may lead to the conflict between phylogenetic susceptibilities, inherited from the process of species evolution, and the cultural needs. The ethicals solution, given by Skinner to this conflict, seems to be the choice for the good of the culture. According to Skinner, a well planned culture guarantees its own survival and, by the same time, guarantees individual welfare.
Keywords: Ethics; conflict; radical behaviorism; good of the culture